SAE Technical Paper Series 2017
DOI: 10.4271/2017-01-1529
|View full text |Cite
|
Sign up to set email alerts
|

Complete Body Aerodynamic Study of three Vehicles

Abstract: Cooling drag, typically known as the difference in drag coefficient between open and closed cooling configurations, has traditionally proven to be a difficult flow phenomenon to predict using computational fluid dynamics. It was seen as an academic yardstick before the advent of grille shutter systems. However, their introduction has increased the need to accurately predict the drag of a vehicle in a variety of different cooling configurations during vehicle development. This currently represents one of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Literature revealed that the selection of turbulence model alone can result in significantly different predictions in many engineering applications. 1922 As far as the road vehicle external aerodynamic studies are concerned, the turbulence modeling effects on RANS predictions are considerably explored with simplified vehicle models, most commonly, the Ahmed body and the DrivAer model, 2325 as well as various types of passenger vehicles; 26,27 recent studies by Fu et al 28,29 are probably the only one related to stock racecar applications. However, since the racecar’s aerodynamic features can be very different under yaw and/or pitch and these racecars are intentionally made asymmetric, observations based on straightway attitudes may not be valid.…”
Section: Introductionmentioning
confidence: 99%
“…Literature revealed that the selection of turbulence model alone can result in significantly different predictions in many engineering applications. 1922 As far as the road vehicle external aerodynamic studies are concerned, the turbulence modeling effects on RANS predictions are considerably explored with simplified vehicle models, most commonly, the Ahmed body and the DrivAer model, 2325 as well as various types of passenger vehicles; 26,27 recent studies by Fu et al 28,29 are probably the only one related to stock racecar applications. However, since the racecar’s aerodynamic features can be very different under yaw and/or pitch and these racecars are intentionally made asymmetric, observations based on straightway attitudes may not be valid.…”
Section: Introductionmentioning
confidence: 99%
“…In the CFD calculation, iterations of the pressure and velocity equations have not converged in all cases (described later in Computational costs). Simmonds et al (2017) [23] pointed out that the RANS analysis for the DrivAer model using k-omega SST turbulence model experienced fluctuations due to a pseudo-unsteadiness in the flow. We consider that the pseudo-unsteadiness appears in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Elements around vehicle's geometric has been applied using inflation layer. Inflation layer is 20 cell height with corresponding y+ value near 35 [9]. As turbulence model, in simulation, was used k-ω Shear Stress Transport (SST).…”
Section: Methodsmentioning
confidence: 99%